The principles of Deleuzian philosophy - Kokubun, Kōichirō, 1974- (Plateaus., 2020)
Koichiro Kokubun focuses on Deleuze's method of 'free indirect discourse' to locate and explicate Deleuze's philosophy of transcendental empiricism and its constitutive limits. He works through Deleuze's confrontations with Hume, Kant, Bergson, Freud, Lacan, Foucault and Guattari, and the influence of structuralism and psychoanalysis.